L16 Taguchi Orthogonal Array Experimental Set Up (International Journal of Communication Systems and Network Technologies, 2021)
One of the major developments in production engineering over 20 years is the application of numerically controlled machine tools in production. It is for sure that CNC application first started with “AEROSPACE” Industries to manufacture highly complex parts that are made up of light alloys, having a better material removal. In this study the experiment were conducted based on L16 Taguchi orthogonal array. The Taguchi method plus Grey Relational Analysis was utilised for solving multi-optimization criteria and Artificial Neural Network model based on Levenberg-Marquardt backpropagation algorithm is used for prediction purpose.
Keywords: CNC Turning; Taguchi; Grey Relational Analysis; ANOVA; Artificial Neural Network; Surface Roughness; Material Removal Rate